Monetary Policy with a touch of Basel - Chami, Ralph (IMF Working Papers; Working Paper, 2001)
The typical portrait of monetary policy has the banks and the money supply being manipulated through changes in bank reserves. However, with only a small portion of bank deposits now subject to reserve requirements, an alternative explanation of how monetary policy influences banks is needed. Over the last decade, capital requirements have effectively replaced reserve requirements as the main constraint on the behavior of banks. This paper explores the implications of Basel capital requirements for monetary policy. In particular, we identify a "bank balance-sheet channel" of monetary policy, which operates through the impact on the money stock and the economy.